Description of the larva of Dorcatoma Herbst, 1791 (Coleoptera: Ptinidae: Dorcatominae), with comments on morphological convergence - Wagner, Grzegorz K.; Staniec, Bernard; Sapieja, Mateusz; Zagaja, Mirosław; Pietrykowska-Tudruj, Ewa (Zootaxa, 2020)
This is the morphological description of the mature larva of a member of the genus Dorcatoma Herbst, 1791. It is also one of the most detailed morphological descriptions of an immature stage of the subfamily Dorcatominae Thomson. Complete characteristics of the head, mouthparts, thorax and abdomen are given. Information relating to morphological convergence with other coleopteran families and the ecology of the species described is also provided.